2009
DOI: 10.1007/s10067-009-1140-0
|View full text |Cite
|
Sign up to set email alerts
|

Development of leprosy in a patient with ankylosing spondylitis during the infliximab treatment: reactivation of a latent infection?

Abstract: The use of tumor necrosis factor alpha as a treatment for chronic inflammatory conditions has been shown to be associated with an increased risk of developing infections, especially Mycobacterium tuberculosis, atypical mycobacteria, and other microorganisms. We report the case of a 58-year-old man with ankylosing spondylitis, receiving infliximab treatment, who presented with multiple plaques on the face, chest, and extremities, a thickened, tender ulnar nerve, and severe neuritis of the feet. The results of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…It was shown that the surface proteins ESAT-6 and CFP-10 used in the QTF test are also present in M. leprae [17]. Moreover, reactivation of leprosy was reported in three patients who were using TNF-α antagonists [18-20]. However, the QTF test had not been studied among patients with leprosy.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the surface proteins ESAT-6 and CFP-10 used in the QTF test are also present in M. leprae [17]. Moreover, reactivation of leprosy was reported in three patients who were using TNF-α antagonists [18-20]. However, the QTF test had not been studied among patients with leprosy.…”
Section: Introductionmentioning
confidence: 99%
“…Several case reports and case series have described new development, reactivation, worsening, or accelerated progression of leprosy, with or without leprosy reactions, in patients exposed to biologics (such as infliximab, adalimumab, etanercept, and abatacept) for the treatment of different inflammatory immunemediated diseases, such as RA, ankylosing spondylitis, psoriatic arthritis, and psoriasis (84)(85)(86)(87)(88)(89). Usually, the biologic was discontinued after the diagnosis, but in some cases, it was reinstituted after the completion of anti-leprosy multi-drug therapy.…”
Section: Leprosy and Immunobiologics Therapymentioning
confidence: 99%